The welfare state and the British classical school - Ζουμπουλάκης, Μιχαήλ (SPOUDAI Journal of Economics and Business, 2002)
The aim of this essay is to trace the origins of the so-called Welfare State in the works of the British Classical School. The "industrial revolution" in Britain provoked deep social transformation and revealed many urgent unprecedented social problems. Economists and social thinkers such as A. Smith, J. Bentham, J.R. McCulloch, N.W. Senior and J.S. Mill, facing these problems developed, along with their theoretical work, the principles of Social Policy in a liberal society. JEL Classifications: B12, H11, Ι30